Pengaruh Brain Based Learning Berbantuan Wordwall Terhadap Hasil Belajar Kognitif Pada Materi Peralatan Optik - Indah Mayanda; Y Yennita; Nur Islami (Postgraduate, University of Mataram, 2024)
Improving student learning outcomes will always be influenced by how teachers teach and provide innovation in learning. This study focuses on evaluating the cognitive learning achievements of class XI high school physics students in the Optical Instrument material, using the Wordwall-assisted Brain Based Learning model. The study is a quasi-experiment with all students in class XI of MS SMAN Plus Riau Province. A sample of 59 students with class XI MS 1 as the experimental group and class XI MS 4 as the control group. Daily tests were conducted to collect data on cognitive learning outcomes, which were analyzed both descriptively and inferentially. The findings indicate a significant difference in cognitive learning outcomes between the experimental and control groups, with the former achieving an average outcome of 81.83 and the latter attaining an average of 73.10. These results demonstrate that the Wordwall-assisted BBL learning model can enhance the cognitive learning outcomes of grade XI students in Senior High School, specifically in the Optical Equipment material.